Aromatic Interactions in Organocatalyst Design: Augmenting Selectivity Reversal in Iminium Ion Activation. Issue 28 (15th May 2015) - Holland, Mareike C.; Metternich, Jan Benedikt; Daniliuc, Constantin; Schweizer, W. Bernd; Gilmour, Ryan
Abstract Invited for the cover of this issue is the group of Ryan Gilmour at the Westfälische Wilhelms‐Universität Münster. The image depicts how the modes of stereoinduction differ for N‐methylpyrrole to N‐methylindole. Read the full text of the article at 10.1002/chem.201500270.